Proteinase Activated Receptor 4 in the Jejunum of Healthy Horses and of Horses With Epiploic Hernia - Lambertini, Carlotta; Bombardi, Cristiano; Zannoni, Augusta; Bernardini, Chiara; Dondi, Francesco; Morini, Maria; Rinnovati, Riccardo; Spadari, Alessandro; Romagnoli, Noemi (Frontiers in Veterinary Science, 2020)
Proteinase activated receptor 4 (PAR4) in the gastrointestinal tract is involved in the regulation of inflammation and pain pathways. The aim of the present study was to evaluate the distribution and expression of PAR4 in the jejunum of healthy horses and in the ischemic tracts from horses undergoing surgery for herniation of the small intestine through the epiploic foramen. Eight healthy horses (Group H) and eight horses with epiploic hernia (Group EH) were included; the jejunum samples were collected at the slaughter or intraoperatively after enterectomy, respectively. To evaluate PAR4 expression in sections of the jejunum, immunofluorescence, western blot and quantitative polymerase chain reaction (qRT-PCR) were performed. Immunohistochemistry of PAR4 in the jejunum of the healthy horses showed that receptors are predominantly espressed in the cellular infiltrates scattered throughout the lamina propria of the mucosa and in the submucosa. Quantitative PCR data demonstrated that PAR4 mRNA was detectable in all of the samples analysed without any difference between the H and the EH groups, however the PAR4 protein level was significantly lower in the jejunums of the EH horses. In the Group EH horses, PAR4 immunoreactivity was mainly expressed in the mast cells and was extensively distributed in the sierosa. In the lamina propria of mucosa of Group EH, leukocytes were less abundant than in Group H. In this study, the distribution and expression of PAR4 in the jejunums of the healthy horses and in those with spontaneous occurring epiploic hernia was demonstrated.